E-learning- A New Trend of Learning in 21st Century During Covid-19 Pandemic (Indian Journal of Forensic Medicine & Toxicology, 2020)
The dissemination of COVID-19 has contributed to the closing of educational institutions around the world.Such closing accelerated the creation of online learning environments within these institutions, ensuringthat learning would not be interrupted. The coronavirus pandemic tested the ability of the centers to copewith a problem that involves online and remote intervention. Most have not been educated, so it is necessaryto investigate the motives for providing online classes to students, which go beyond the confinement era.The vast majority of children have no previous experience of remote learning previous to the pandemic.Since the COVID-19 pandemic has destroyed people’s usual lifestyles around the globe, the virtual worldhas come to the rescue. Like several institutions, schools have already transferred their focus to interactivenetworks to take classes online. Video conferencing tools such as Zoom and WebEx are commonly usedand learning management systems such as Infrastructure Canvas, Blackboard and Google Classroom. Inaddition, applications such as Proctorio, a Google Chrome plugin that tracks students taking online tests,are available. In India, too, all educational institutions have been suspended by the government as part ofthe national lockdown, which has impacted learners ranging from school-learning to post-graduate students.